Biological responses to flexion/extension in spinal segments ex‐vivo. Issue 8 (27th April 2015) - Hartman, Robert A.; Yurube, Takashi; Ngo, Kevin; Merzlak, Nicolas E.; Debski, Richard E.; Brown, Bryan N.; Kang, James D.; Sowa, Gwendolyn A.
ABSTRACT Mechanical loading is a salient factor in the progression of spinal disorders that contribute to back pain. Biological responses to loading modes like flexion/extension (F/E) in relevant spinal tissues remain unstudied. A novel, multi‐axial experimental system was developed to subject viable functional spinal units (FSUs) to complex, in‐situ loading. The objective was to determine biological effects of F/E in multiple spinal tissues—annulus fibrosus, nucleus pulposus, facet cartilage, and ligamentum flavum. Rabbit lumbar FSUs were mounted in a bioreactor within a robotic testing system. FSUs underwent small (0.17/0.05 Nm) and large (0.5/0.15 Nm) range‐of‐motion F/E for 1 or 2 h of cycling. Outcomes in each tissue, compared to unloaded FSUs, included (i) relative mRNA expression of catabolic (MMP‐1, 3 and ADAMTS‐5), pro‐inflammatory (COX‐2), and anabolic (ACAN) genes and (ii) immunoblotting of aggrecan degradation. Total energy applied to FSUs increased in groups subject to large range‐of‐motion and 2‐h cycling, and moment relaxation was higher with large range‐of‐motion. F/E significantly modulated MMP1, ‐3 and COX‐2 in facet cartilage and MMP‐3 and ACAN in annulus fibrosus. Large range‐of‐motion loading increased MMP‐mediated aggrecan fragmentation in annulus fibrosus. Biological responses to complex loading ex vivo showed variation among spinal tissues that reflect tissue structure and mechanical loading in F/E. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1255–1264, 2015.